If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-4) = 5(x + -3) Multiply -1 * -4 y + 4 = 5(x + -3) Reorder the terms: 4 + y = 5(x + -3) Reorder the terms: 4 + y = 5(-3 + x) 4 + y = (-3 * 5 + x * 5) 4 + y = (-15 + 5x) Solving 4 + y = -15 + 5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = -15 + -4 + 5x Combine like terms: 4 + -4 = 0 0 + y = -15 + -4 + 5x y = -15 + -4 + 5x Combine like terms: -15 + -4 = -19 y = -19 + 5x Simplifying y = -19 + 5x
| -19+x=14 | | 17.8x+5[6-(2x+3)]= | | P^2+2p-24= | | -(1-(-2)2)2-5x(-2)= | | 324=2X+(X-84) | | 24+7x=9x+14 | | x-(-11)=17 | | y+4x-2=0 | | -6x-10=19-5x | | 13+x=-20 | | 3*4.5-y=9 | | 2x^2+3y^2+12x-12y-210=0 | | 7(2x+9)=3x+100 | | 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) | | 4m-9= | | 6+3*5-2=5 | | 2(3x+2)+6(2x-1)=40 | | 13x-4=2x+4 | | -72=-8(4-2x)-8(1-2x) | | 13x-4=2x+2 | | 2p=96-10 | | 5p-7p=3p+1 | | 13x+4=-5x+1 | | -86=-2(1-6a) | | 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 | | 4(2x-5)=43 |